Retrospective study of hepatitis c virus relapse after treatment with sofosbuvir and daclatasvir with or without ribavirin - Mohamed DA Abd Alla; Amer AA Gomaa; Galal A Abou Farrag; Mohamed G Shikhroho; Walid M Mousa; Osama AM Mahmoud (Wolters Kluwer Medknow Publications, 2018)
Background and aims The highest prevalence of chronic hepatitis C virus (HCV) genotype 4 infection is reported in Egypt. Fortunately, the oral anti-HCV therapy (OAT) has been available with more than 95% reported 12-week sustained virologic response (SVR) after treatment for 84 days. The current study goals included evaluation of 12-week SVR after treatment with sofosbuvir (SOF) plus daclatasvir (DCV) with or without ribavirin for 12 weeks. An additional goal was to study the correlation between post-OAT HCV serologic relapse and diabetes mellitus, liver fibrosis, and pretreatment viral loads. Patients and methods Patients with chronic HCV infection (n=590) were retrospectively enrolled in the current study. They were subjected to OAT for 12 weeks. Single daily dose of SOF (400 mg) plus DCV (60 mg) constituted the baseline therapy in all study cases, and ribavirin (RBV) was coadministered in 262 patients. Responses to OAT were assessed 12 weeks after end of treatment by single-step reverse transcription polymerase chain reaction (SRT-PCR). Results We found that overall 12-week SVR was 98% (579/590), which showed insignificant advantages on adding ribavirin (99%) compared with solitary directly acting antivirals regimen (97%) (P>0.05). The SVR in normoglycemic and/or none or early hepatic fibrosis (F0-F2) (>99.0%) was significantly higher compared with diabetic and/or late fibrotic (F3-F4) (94%) patients (P<0.05). Pretreatment detection of HCV loads by SRT-PCR was significantly lower in F0 compared with F4 hepatic fibrosis (P<0.001), with insignificant changes when compared with F1-F3 (P>0.05). Conclusion SOF plus DCV with or without ribavirin regimens achieved 12-week SVR in 98% of the patients with chronic HCV infection. Hepatic fibrosis and diabetes mellitus have negative effects on 12-week SVR. Despite F4 hepatic fibrosis being associated with the highest pre-treatment HCV-SRT-PCR values, baseline viral loads do not affect anti-HCV oral therapy outcomes.